Hubungan antara Pengambilan Keputusan dengan Perilaku Kontraproduktif Guru SMP Negeri di Kota Bekasi - Bella Meilia Saputra; Dwi Deswary; Eliana Sari (Program Studi Manajemen Pendidikan, 2017)
This study aims to determine the relationship between decision making and counterproductive behavior Junior High School teacher in Bekasi. The method used is survey method with the correlational studies and quantitative approaches. Samples were as many as 94 teachers. Sampling using simple random sampling by the formula Slovin and data collection using the questionnaires. From the results of the hypothesis testing, obtained tcount equal to 2,10, which means bigger than ttable 1,986. Thus, the alternative hypothesis (Ha) are accepted positively. Of the coefficient of determination, decisionmaking contributed 4.57% to the counterproductive behavior Junior High School teacher in Bekasi. Based on the results of the survey results revealed that more favorable decision, the lower the level of counterproductive behavior Junior High School teacher in Bekasi.